13C pathway analysis of biofilm metabolism of Shewanella oneidensis MR-1. Issue 50 (4th June 2015) - Guo, Weihua; Luo, Shuai; He, Zhen; Feng, Xueyang
<x xml:space="preserve">Abstract</x> Biofilm metabolism of Shewanella was analyzed via13C tracing experiments for the first time.